Laparoscopic radical prostatectomy: a single center experience - Shabani, Bashkim (Acta medicae Medianae, 2020)
Minimally invasive techniques including robotic-assisted and laparoscopic radical prostatectomy have become the preferred approach for operative treatment of prostate cancer. The aim of this study was to evaluate and compare results of laparoscopic radical prostatectomy (LRP) and open retropubic radical prostatectomy (ORRP) for localised prostate cancer, in terms of safety, eficacy and oncological outcome.A total of 123 radical prostatectomies (RPs) for low-risk localised prostate cancer were performed between January 2016 and June 2019 at the University Clinic of Urology Skopje. Of these, 61 (49.6%) were LRP and 62 (50.4%) ORRP, mean patients age was 54 years (33 to 67)  Indications for operative procedure included: pathohistological finding of prostate cancer, age ≤ 70 years, PSA
Keywords: prostate cancer, laparoscopic radical prostatectomy, open retropubic radical prostatectomy